Seruan Apostolik Christus Vivit Terhadap Dampak Negatif Artificial Intelligence Bagi Kaum Muda - Satrio, Didimus Adventus; Tukan, Antonius Nggino; Abatan, Yofince (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This research aims to examine the role of the Apostolic Exhortation Christus Vivit in overcoming the negative impact of Artificial Intelligence (AI) on young people. AI, as a technological advancement, offers convenience in various aspects of life, but also has negative impacts such as decreased intellectual independence, individualism, and disruption of emotional and social well-being. The method used is qualitative research through literature analysis. The main source used is the Apostolic Exhortation Christus Vivit and additional sources are research journals and books related to this research. The research results show that Christus Vivit provides important direction for young people to develop intellectual and spiritual abilities independently, reduce dependence on AI, and improve social relations. The research also found that AI, if used wisely, can be an enabling tool that enriches the lives of young people. In conclusion, although AI is not a threat that must be rejected, its use requires a critical attitude and awareness so that young people continue to prioritize their God-given intellectual, emotional and spiritual abilities.